Analysis of Dioxins Concentration in Domestic Waste and Burnt Tyre Residue at Gosa Dumpsite in Abuja, Nigeria - M.M, Alhassan; M, Struve; J.I, Oleka; F, Ujoh (Review of Environment and Earth Sciences, 2015)
This study examined the presence of dioxins – a persistent organic pollutant in domestic and burnt tyre waste residues and it’s comparison with German safety limits at the Gosa dumpsite in Abuja, Nigeria. The period of sampling and analysis was between January and March, 2011. Burnt tyre ashes and burnt solid waste residues from the dump sites were chemically analyzed to determine the concentration of the seventeen 2,3,7,8-substituted dioxins and furan congeners in absolute quantities using high resolution capillary column gas chromatography and low resolution mass spectrometry. The result of the analysis performed using the International Toxic Equivalent Factor (NATO/CCMS) for the calculation of the individual Toxic Equivalent Quotients (TEQs) of the seventeen 2,3,7,8- substituted dioxins and furan congers and a summation of the individual I-TEQs per sample shows that there is significant quantity of about 44 ng/kg TM of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a contaminant in Agent Orange, in one out of the five (1/5) analyzed samples. The maximum Total Polychlorinated dibenzo-p-dioxins/furans (PCCD/F) concentration recorded in this study was 1,350 ng/kg TM from sample Point 3. This was greater than the German Federal Soil Protection and Contamination Sites Ordinance (GFSPCSO) for Total PCDD/F equivalents for target concentration, agricultural, playground and residential landuse (which dominate the area under study) but less than its industrial landuse equivalent. There was also the presence of dioxins in the burnt domestic waste analysed with the Total PCDD/F (TEQ) of 6.6 ng/kg TM. The land usage of the area under investigation is closely interwoven across the land mass. Therefore, the results indicate that the population and activities within the area of study are under threat of health hazards that may arise from the high concentration of dioxins recorded by this study.